TOOLKIT OF THE MECHANISM FOR ENSURING SUSTAINABLE DEVELOPMENT OF ENTREPRENEURSHIP IN THE CONDITIONS OF POST-WAR RECOVERY OF THE ECONOMY OF UKRAINE - Дубіна, Микола І. (Journal of Strategic Economic Research, 2025)
The article reflects the key aspects of ensuring sustainable development of entrepreneurship through the tools of the management mechanism. A set of methods has been formed in the area of this issue and a toolkit of economic, organizational, innovative elements has been substantiated, aimed at balancing economic, environmental and social goals, increasing competitiveness and adaptability, which includes grant support, digitalization of processes, corporate social responsibility and effective management. The formed economic and financial tools are undoubtedly state grant support, facilitated access to international programs, investments in "green" technologies and energy efficiency. Organizational and management tools: Strategic planning based on sustainable development, adaptive and flexible management systems, risk management, environmental audit and monitoring of activities. Innovative and digital tools: Implementation of digital technologies, automation of business processes, development of innovative activities to increase productivity. Socio-ethical tools: Corporate social responsibility, training and development of personnel, adherence to ESG (Environmental, Social, Governance) principles. Regulatory tools: Simplification of business conditions, state support through procurement, partnership between the state and the private sector. The institutional component and regulatory and legal support of the mechanism for ensuring sustainable development of entrepreneurship in the conditions of post-war economic recovery of Ukraine are analyzed.